Digital coin box - Mohd Said, Muhammad Iskandar; Mohamad Najib, Mohamad Nazril Syah (2016)
The digital coin box is designed to save up their coin. But nowadays, technology have improved in our world. People also have been busy doing their own job and it is unable give their time to save up their money in the bank. The system of the coin box is mostly like a vending machine. It used a coin detector to detect coin that inserted in a box. Also a combination like a security box system that used a passcode for a security. The microcontroller PIC16F877A is used as brain to control the digital coin system, where the programming language used for developing the software to the microcontroller is C-language. Finally, the system has been successfully designed and implemented as prototype system.